2013
DOI: 10.1111/ecc.12165
|View full text |Cite
|
Sign up to set email alerts
|

Loss, uncertainty, or acceptance: subjective experience of changes to fertility after breast cancer

Abstract: This qualitative study examines the subjective experience of infertility in a large sample of Australian women with breast cancer. Participants were 1830 women, average age 54, who responded to an email invitation to complete an online survey on sexual well-being and fertility concerns after breast cancer. 24.6% (n = 452) reported that cancer had affected their fertility; 21.3% (n = 391) did not know their fertility status. In thematic analysis of open-ended responses provided by 381 women about changes to fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 44 publications
3
70
0
4
Order By: Relevance
“…A study among 484 male and female cancer survivors showed that parental status and age were associated with a change in the desire to have children (Armuand, Wettergren, Rodriguez-Wallberg, & Lampic, 2014). Qualitative research has provided valuable insight into male and female survivors' experiences of compromised fertility (Perz, Ussher, & Gilbert, 2014;Wong et al, 2017) and the complexity involved in the decision to have children following cancer (Hsieh et al, 2017). Qualitative research has provided valuable insight into male and female survivors' experiences of compromised fertility (Perz, Ussher, & Gilbert, 2014;Wong et al, 2017) and the complexity involved in the decision to have children following cancer (Hsieh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A study among 484 male and female cancer survivors showed that parental status and age were associated with a change in the desire to have children (Armuand, Wettergren, Rodriguez-Wallberg, & Lampic, 2014). Qualitative research has provided valuable insight into male and female survivors' experiences of compromised fertility (Perz, Ussher, & Gilbert, 2014;Wong et al, 2017) and the complexity involved in the decision to have children following cancer (Hsieh et al, 2017). Qualitative research has provided valuable insight into male and female survivors' experiences of compromised fertility (Perz, Ussher, & Gilbert, 2014;Wong et al, 2017) and the complexity involved in the decision to have children following cancer (Hsieh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that impaired fertility from cancer treatment has a negative impact on quality of life for cancer survivors. The psychological impact of cancer-related infertility is comprised of emotional distress, reproductive concerns, loss of identity, depression, and grief (Carter et al, 2005(Carter et al, , 2010Gorman, Bailey, Pierce, & Su, 2012;Perz, Ussher, & Gilbert, 2014). Infertility can also place strain on couples' relationships (Penrose, Beatty, Mattiske, & Koczwara, 2013;Perz et al, 2014).…”
mentioning
confidence: 99%
“…The psychological impact of cancer-related infertility is comprised of emotional distress, reproductive concerns, loss of identity, depression, and grief (Carter et al, 2005(Carter et al, , 2010Gorman, Bailey, Pierce, & Su, 2012;Perz, Ussher, & Gilbert, 2014). Infertility can also place strain on couples' relationships (Penrose, Beatty, Mattiske, & Koczwara, 2013;Perz et al, 2014). Single cancer survivors with the potential for fertility problems may experience difficulties in starting new relationships because of past rejection or the fear of being rejected by a potential partner (Zebrack, Casillas, Nohr, Adams, & Zeltzer, 2004).…”
mentioning
confidence: 99%
“…Peate et al, 2011;Perz et al, 2014), these results highlight the need to implement strategies that help to generalise the FP discussion and referral practices. Peate et al, 2011;Perz et al, 2014), these results highlight the need to implement strategies that help to generalise the FP discussion and referral practices.…”
Section: Practices Of Oncologists Regarding Fpmentioning
confidence: 91%
“…In Portugal, despite the availability of male FP since the 1990s in several clinical institutions, female FP techniques are only offered since 2010; both male and female FP options are funded by the Portuguese National Healthcare System. Cancer-related infertility has been shown to have a negative impact on the individual adaptation of female cancer survivors (Carter et al, 2010;Loscalzo & Clark, 2007;Perz, Ussher, & Gilbert, 2014), so this topic deserves further attention. Cancer-related infertility has been shown to have a negative impact on the individual adaptation of female cancer survivors (Carter et al, 2010;Loscalzo & Clark, 2007;Perz, Ussher, & Gilbert, 2014), so this topic deserves further attention.…”
Section: Introductionmentioning
confidence: 99%